Performance Reviewed from Leadership, Human Resource Professionalism, Motivation and Work Discipline of Teachers at State Senior High School 1 Purwantoro - Paryani Paryani; Istiatin Istiatin; Sudarwati Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Teacher performance is a critical determinant of educational quality and institutional effectiveness. This study aims to examine and analyze the influence of leadership, human resource professionalism, motivation, and work discipline on teacher performance at SMA Negeri 1 Purwantoro, Wonogiri Regency. This research employed a descriptive quantitative approach. The population comprised all teachers at SMA Negeri 1 Purwantoro, totaling 53 individuals. A non-probability sampling technique with a census method was applied, in which the entire population was used as the research sample. The results indicate that leadership has a positive and significant effect on teacher performance. Similarly, human resource professionalism exerts a positive and significant influence on teacher performance. Motivation and work discipline were also found to have positive and significant effects on teacher performance. In conclusion, leadership, human resource professionalism, motivation, and work discipline are key determinants that significantly enhance teacher performance at SMA Negeri 1 Purwantoro. Keywords:teacher performance, leadership, human resource professionalism, motivation, work discipline